Peningkatan Perkembangan Bahasa Aud Melalui Permainan “Celemek Bimsalabim” Di Tk Shafiya Smart School Tahun Ajaran 2021/2022 - Titik Rahayu Ningsih; Sri Haryanto; Hidayatu Munawaroh (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Institut Pesantren Mathali'ul Falah Pati, 2022)
Language development is one of the most critical developments in Early Childhood (AUD) because language development is one of the abilities to master communication tools orally, in writing, or using signs. However, with the various problems faced by children in Shafiya Smart School Kindergarten, researchers are interested in researching the development of AUD language through the game